Computational Identification of the Proteins Associated With Quorum Sensing and Biofilm Formation in Mycobacterium tuberculosis - Hegde, Shubhada R. (Frontiers in Microbiology, 2020)
With prolonged therapy and increased instances of drug resistance, tuberculosis is viewed as a serious infectious disease causing high mortality. Emerging concepts in M. tuberculosis pathogenicity include biofilm formation, which endows bacterial survival in the host for a long time. In order to tackle chronic tuberculosis infection, a detailed understanding of the bacterial survival mechanisms is crucial. Using comparative genomics and literature mining, 115 M. tuberculosis proteins were shortlisted for their likely association with biofilm formation or quorum-sensing. These include essential genes such as secA2, lpqY-sugABC, Rv1176c and Rv0195, many of which are also known virulence factors. Further, three levels of protein interactions, namely, protein-protein, regulatory and expression correlations were used to establish the functional relationship among these proteins. Graph centrality and motif analyses predicted the importance of proteins such as Rv0081, DevR, RegX3, Rv0097 and Rv1996 in M. tuberculosis biofilm formation. Conservation across other biofilm forming bacteria suggests that most these genes are unique to pathogenic mycobacteria. As the processes, such as quorum-sensing leading to biofilm formation involve diverse pathways and interactions between proteins, these system-wide studies provide a novel perspective towards understanding mycobacterial persistence.